2013
DOI: 10.3747/pdi.2012.00215
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Implications of Peritoneal Dialysis in Patients with Acute Kidney Injury

Abstract: ♦ Background: Peritoneal dialysis (PD) is a treatment for selected acute kidney injury patients (AKI), but little is known about its metabolic implications. The aim of the present study was to evaluate the metabolic implications of glucose absorption, sodium removal, protein loss into the dialysate, and catabolism in AKI patients undergoing high-volume PD and to identify risk factors associated with those metabolic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…They showed that protein loss was 4.2 (± 6.1) g/24 h and there was no correlation with albumin levels. Peritonitis did however increase protein loss (63). Care should be taken to ensure that adequate protein intake occurs aiming for approximately 1.2 g/kg of protein per 24 hours.…”
Section: • Peritonitis • Mechanical Complications • Protein Loss • Hymentioning
confidence: 99%
“…They showed that protein loss was 4.2 (± 6.1) g/24 h and there was no correlation with albumin levels. Peritonitis did however increase protein loss (63). Care should be taken to ensure that adequate protein intake occurs aiming for approximately 1.2 g/kg of protein per 24 hours.…”
Section: • Peritonitis • Mechanical Complications • Protein Loss • Hymentioning
confidence: 99%
“…Góes et al [29] performed an interesting prospective cohort study, and evaluated 208 sessions of HVPD in 31 AKI patients, aiming to evaluate metabolic implications and to identify risk factors associated with those metabolic effects. The glucose absorption remained at approximately 35.3 ± 10.5% per session, the protein loss measured 4.2 ± 6.1 g daily, with higher values initially, which declined significantly after 2 sessions, and the NB was initially negative, but stabilized at approximately zero after 3 sessions.…”
Section: Controversiesmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common disorder that affects approximately 30% of patients in intensive care units (ICU) (1). Recent studies have shown that peritoneal dialysis (PD) can be an option for select AKI patients for promoting adequate metabolic and fluid control with a mortality rate similar to that of other dialysis modalities (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%